The New Zealand (School Curriculum) ‘History Wars’: The New Zealand Land Wars Petition and the Status of Māori Histories in New Zealand Schools (1877–2016) - Manning, Richard (The Australian Journal of Indigenous Education, 2017)
This article draws upon historical evidence and theoretical insights to critique the New Zealand government's negative response to a popular petition developed by students of Otorohanga College. The petition called for the New Zealand Land Wars to become a ‘prescribed course of study’ (topic) in New Zealand schools. This article consequently reviews the status of Māori histories in New Zealand schools from 1877 to 2016. This review is followed by a critique of the New Zealand government's response to the petition. This will be of interest to an Australian audience grappling with issues relating to the teaching of Indigenous peoples’ histories in schools.